POLITICAL ANTHROPOLOGY AS METHOD - Szakolczai, Árpád. ([S.l.])
1 online resource
Keywords: This book explores considerations of method in the field of political anthropology, contending that this constitutes a distinct approach within the broader area of the human, social and political sciences. Faithful to the basic guiding ideas of anthropology, it nonetheless challenges and rejects the pretended stance of scientific neutrality and advances a position that engages with the notion of participation, recognising its value and arguing that participation is essential to the development of a proper social and political understanding. An outline of what political anthropology can offer by way of methods, this invitation to consider the development of methodological ideas beyond the presumed scientific' and universalistic' approaches that dominate in the social sciences will appeal to scholars of anthropology, sociology and politics with interests in questions of method and methodology.